DESIGN OF IRRIGATION CHANNEL SYSTEM TO PROMOTE MODERN AGRICULTURE IN JALLE-PAYAM BOR, SOUTH SUDAN. - Moses Bior Abraham Pandek; Ratih Indri Hapsari; Winda Harsanti (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
This study aims to promote and improve modern agricultural practices by addressing the critical need for building a well-designed irrigation channel system in Jalle-Payam Bor, South Sudan. The lack of a substantial irrigation infrastructure has hampered the region's agricultural potential, resulting in inadequate crop yields and an emphasis on rain-fed agriculture. To overcome these issues, this research focuses on comprehensive planning and design solutions for an effective irrigation network adapted to the Jalle-Payam Bor region's specific demands and environment. The fundamental goal of this thesis is to promote and improve modern agricultural practices by addressing the critical need for building a well-designed irrigation channel system in Jalle-Payam Bor, South Sudan Based on the facts and analysis presented in Chapter 4, the Jalle Irrigation Channel System is intended to enable modern agriculture in Jalle-Payam Bor, South Sudan. The plan efficiently distributes water across 76 plots totaling 100 hectares, resulting in uniform water dispersion and higher agricultural productivity. The maximum irrigation water need of 1.487 liters per second per hectare was precisely calculated, ensuring adequate water delivery to meet crop demands. The program consumes only 0.8% of the Nile Water Discharge, ensuring a consistent water supply even during dry spells, and has the potential to expand if other conditions allow. The irrigation channels are well-designed, with capacities ranging from 1.575 to 0.093 cubic meters per second, ensuring effective water supply and ideal velocities. The project has a solid budget of Rp 605.456.372,23 ($37,132.64), which includes all material, labor, and equipment expenditures, ensuring economic feasibility and sustainability.